Bi-allelic Loss-of-Function Variants in NUP188 Cause a Recognizable Syndrome Characterized by Neurologic, Ocular, and Cardiac Abnormalities. - Muir, A.M.; Cohen, J.L.; Sheppard, S.E.; Guttipatti, P.; Lo, T.Y.; Weed, N.; Doherty, D.; DeMarzo, D.; Fagerberg, C.R.; Kjærsgaard, L.; Larsen, M.J.; Rump, P.; et al. (American Journal of Human Genetics, 2020)
Nucleoporins (NUPs) are an essential component of the nuclear-pore complex, which regulates nucleocytoplasmic transport of macromolecules. Pathogenic variants in NUP genes have been linked to several inherited human diseases, including a number with progressive neurological degeneration. We present six affected individuals with bi-allelic truncating variants in NUP188 and strikingly similar phenotypes and clinical courses, representing a recognizable genetic syndrome; the individuals are from four unrelated families. Key clinical features include congenital cataracts, hypotonia, prenatal-onset ventriculomegaly, white-matter abnormalities, hypoplastic corpus callosum, congenital heart defects, and central hypoventilation. Characteristic dysmorphic features include small palpebral fissures, a wide nasal bridge and nose, micrognathia, and digital anomalies. All affected individuals died as a result of respiratory failure, and five of them died within the first year of life. Nuclear import of proteins was decreased in affected individuals' fibroblasts, supporting a possible disease mechanism. CRISPR-mediated knockout of NUP188 in Drosophila revealed motor deficits and seizure susceptibility, partially recapitulating the neurological phenotype seen in affected individuals. Removal of NUP188 also resulted in aberrant dendrite tiling, suggesting a potential role of NUP188 in dendritic development. Two of the NUP188 pathogenic variants are enriched in the Ashkenazi Jewish population in gnomAD, a finding we confirmed with a separate targeted population screen of an international sampling of 3,225 healthy Ashkenazi Jewish individuals. Taken together, our results implicate bi-allelic loss-of-function NUP188 variants in a recessive syndrome characterized by a distinct neurologic, ophthalmologic, and facial phenotype.